1976
DOI: 10.1677/joe.0.0680297
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen as an Anti-Tumour Agent: Effect on Oestrogen Binding

Abstract: Tamoxifen (ICI 46,474) has been shown to possess anti-tumour properties in the dimethylbenz(a)anthracene (DMBA)-induced rat mammary carcinoma model. During tamoxifen therapy the binding of [3H]oestradiol in vivo to uterine (P less than 0-001), vaginal (P less than 0 X 01) and tumour (P less than 0-001) tissues was significantly reduced. Tamoxifen therapy was without effect on the binding of [3H]oestradiol in heart tissue. The determination of specific oestrogen-binding components in vitro was significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 22 publications
1
46
0
1
Order By: Relevance
“…In general there was no difference in the extent to which hormones were suppressed by these agents in responders and non-responders to therapy. Responders Similarly, the effect of tamoxifen on gonadotrophin concentrations is likely to be a secondary effect, since it is known that the major site of action of the drug is on RE (Jordan & Dowse, 1976). However, we have demonstrated that after tamoxifen therapy, the tumour is RE- (Taylor et al, in press), suggesting that tamoxifen is still capable of binding to RE on relapse or non-response.…”
Section: Discussionmentioning
confidence: 72%
“…In general there was no difference in the extent to which hormones were suppressed by these agents in responders and non-responders to therapy. Responders Similarly, the effect of tamoxifen on gonadotrophin concentrations is likely to be a secondary effect, since it is known that the major site of action of the drug is on RE (Jordan & Dowse, 1976). However, we have demonstrated that after tamoxifen therapy, the tumour is RE- (Taylor et al, in press), suggesting that tamoxifen is still capable of binding to RE on relapse or non-response.…”
Section: Discussionmentioning
confidence: 72%
“…However, a strategic plan was developing to use tamoxifen in a broader range of patient populations. Laboratory studies conducted in the 1970's showed that tamoxifen blocked estrogen binding to the ER [15][16][17], should be used as a long-term adjuvant therapy to suppress tumor recurrence [18][19][20] and the drug also had potential as a chemopreventive agent [21,22].…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…The secondary hypothesis to be addressed was that only ER positive disease would respond as tamoxifen and metabolites blocked the binding of [ 3 H]-oestradiol to tumour ER [39,[68][69][70].…”
Section: Laboratory Modelmentioning
confidence: 99%